(untitled) (Ameghiniana, 2020)
Astrapotheres were a clade of unusual early to middle Cenozoic herbivorous mammals endemic to South America. Neogene astrapotheres were large, tusked mammals that probably had a short proboscis and may have preferred mesic lowland habitats; they were widespread during the early Miocene, became restricted to the tropics during the middle Miocene, and apparently did not persist into the late Miocene. the geologically youngest astrapotheres pertain to the subfamily Uruguaytheriinae, and in this report, we describe a partial uruguaytheriine astrapothere cranium with well-preserved postcanine dentition that we identify as Granastrapotherium cf. snorki. this specimen was collected from fluviolacustrine strata in the tumbes Region of extreme northwestern Peru that likely pertain to the Zorritos Formation. At present, the temporal range of Granastrapotherium snorki is restricted to the late middle Miocene (Serravallian Age; ca. 13.6–12.8 Ma), which suggests a similar age for the fossil-bearing sediments of the upper Zorritos Formation. the fossil locality, which is ca. 25 km southwest of the city of tumbes, is ca. 1,000 km distant from other sites in Peru and Colombia where G. snorki has been recorded and extends the geographic range of the species westward more than 550 km. We estimate the body mass of G. snorki at 1,800–2,500 kg based on head-body length of 3.75 m; this is lower than dentition-based body mass estimates but still suggests G. snorki was the largest terrestrial mammal in South America at the time